MODELING TIME-DEPENDENT DEFORMATIONS OF CONCRETE MEMBERS SUBJECTED TO SYMMETRIC AND ASYMMETRIC DRYING - Pavel Horák; Petr Havlásek (Acta Polytechnica CTU Proceedings, 2021)
The time-dependent behavior of concrete members with uniform cross-section subjected to symmetric drying can be predicted with one of many models anchored in the design codes. Since these models use the cross-sectional approach, only the average quantities can be obtained. More complex phenomena can be investigated by means of a coupled hygro-mechanical finite element analysis. Owing to insufficient or missing experimental data, the input parameters for the moisture transport model are often tuned to match the development of axial shrinkage or moisture loss measured on small-scale laboratory specimens. In this paper it is assessed whether this approach leads to a unique set of parameters of the Bažant-Najjar model for moisture diffusion. Additionally, for the selected sets of parameters the analysis is repeated with modified size and/or boundary conditions leading to asymmetric drying and the results are discussed.